Minimal occlusive volume is a safe and effective method for adjusting cuff pressure in mechanically ventilated patients (Fisioterapia e Pesquisa, 2022)
The ideal cuff pressure (Pcuff) must preventmicroaspiration of oropharyngeal secretions due to air leakageand avoid injury to the tracheal mucosa. Usually, monitoringconsists of a manometer to keep the Pcuff between 20 and30cmH2O. The minimal occlusive volume (MOV) methodminimally inflates the cuff using a syringe so that no leakageoccurs. This study aims to evaluate the ability of the minimalocclusive method to individualize the Pcuff adjustment inmechanically ventilated patients. Cross-sectional prospectivestudy with 25 adult patients with more than 48 hours ofmechanical ventilation. Cuff pressure was measured attwo moments: initial and by MOV. The prevalence of Pcuffoutside the normal range was 76%. Leakage in the initialmeasurement occurred in 9 patients, 4 of whom werewithin the reference values. The other 5 patients presentedPcuff<20cmH2O. In the adjustment by the MOV method, all patients presented Pcuff at the limit of normality. Patients withoutleakage with Pcuff>30cmH2O had a reduction when adjusted for MOV(45.4±9.6 against 28.5±1.6cmH2O; p<0.001). We can conclude thatthe minimal occlusive volume method was able to individualize thePcuff within the reference values in all patients.